2
$\begingroup$

I am trying to find the martingale representation of $F = \int_0^TW_t^2dt $.

I wrote that $ \int_0^TW_t^2dt = TW_T^2 - \frac{T^2}{2} - \int_0^T 2tW_t dW_t$ and I'm stuck.

Any ideas on how to proceed?

$\endgroup$
1
  • 1
    $\begingroup$ There's a typo: $2$ should be in front of the integral. $\endgroup$ Dec 30, 2020 at 0:33

1 Answer 1

3
$\begingroup$

As $\frac12 W_{T}^2 - \frac{T}2= \int_{0}^T W_t dW_t$ we may proceed:

$$TW_T^2 - \frac{T^2}{2} - \int_0^T tW_t dW_t =2T(\frac12 W_{T}^2 - \frac{T}2) + \frac{T^2}2 - \int_0^T tW_t dW_t =$$ $$ = \frac{T^2}2 + 2T \int_{0}^T W_t dW_t - \int_0^T tW_t dW_t=$$ $$=\frac{T^2}2 +\int_0^T (2TW_t - tW_t) dW_t .$$

But there's a typo in your formula.

Indeed, by Ito formula $dW_t^2 = 2W_t d W_t + dt$ and thus

$$\int_0^TW_t^2dt = TW_T^2 - 0W_0^2 - \int_0^T t dW_t^2 = TW_T^2 - 0W_0^2 - \int_0^T t (2W_t d W_t + dt) =$$ $$= TW_T^2 - \frac{T^2}{2} - 2\int_0^T tW_t dW_t $$

Thus $$\int_0^TW_t^2dt = TW_T^2 - \frac{T^2}{2} - 2\int_0^T tW_t dW_t = \frac{T^2}2 + 2\int_0^T (T-t)W_tdW_t .$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.